موقف الحديث النبوي الشريف من التعايش مع غير المسلمين: دراسة تحليلية The position of the Prophet's Hadith on coexistence with non-Muslims: An analytical study - Rahman, Shujaur Rahman; Al-Khairabadi, Mohammed Abullais (Universiti Sains Islam Malaysia, 2022)
يهدف هذا البحث إلى بيان موقف الأحاديث النبوية من التعايش مع غير المسلمين ودراستها، مع التعرض لأهميّة الحوار، وأصول التعايش مع المخالف في سياق هذا العصر؛ ليكون نموذجًا يحتذى به في مجاله. واعتمد البحث على المنهج الاستقرائي لتتبع الأحاديث والآثار ذات الصلة بالموضوع، والمنهج التخريجي لتخريج الأحاديث حول الموضوع، واستنباط التصور الكامل للمعاملة مع غير المسلمين وفق المنهج النبوي، والمنهج التحليلي لاستنباط وتحليلي مفاهيم وعناصر التعايش السلمي مع غير المسلمين. ومن أهمّ نتائج البحث أنّ السنة النبويّة بيَّنت ضرورة الاعتراف بغير المسلمين، وأباحت مخالطتهم والتعايش معهم، وكفلت لهم حرِّيَّة العقيدة وممارسة شعائرهم، ومنحتهم حرِّيَّة الرأي والتعبير، وحرِّيَّة التعليم والعمل والتجارة، وكفلت لهم أيضًا العدالة والحماية من الاعتداء، وحسن المعاملة. وأنّ التسامح والتعايش سياسة يحرص عليها الإسلام مع حمايتها مـن التطــرف والطائفيــة، وسماحة النبي ﷺ ورحمته بأمة الدعوة، وحرصه على الحوار بالتي هي أحسن مع غير المسلمين، وضمان عيشهم في المجتمع المسلم، والاحترام والتقدير والكرم مع المخالف في المعتقد والدين، وأن الثبات على المعتقد الصحيح والمبادئ لا يعني الجفاء وسوء التعامل مع المخالف، ولا يتعارض مع التنزل له ورحمته في مجادلته بالحجّة والبرهان بالتي هي أحسن. Research Summary: This research aims to clarify the position of the hadiths of the Prophet on coexistence with non-Muslims and study them, while addressing the importance of dialogue, and the principles of coexistence with the violator in the context of this era; To be a role model in his field. The research relied on the inductive approach to follow the hadiths and effects related to the subject, and the graduate approach to extract the hadiths on the subject, and to devise a complete perception of dealing with non-Muslims according to the Prophet's approach, and the analytical approach to elicit and analyze the concepts and elements of peaceful coexistence with non-Muslims. One of the most important results of the research is that the Sunnah showed the necessity of recognizing non-Muslims, allowed mixing with them and coexisting with them, and guaranteed them freedom of belief and practice of their rituals, and granted them freedom of opinion and expression, and freedom of education, work and trade, and also guaranteed them justice and protection from aggression, and good treatment. And that tolerance and coexistence is a policy that Islam is keen on while protecting it from extremism and sectarianism, and the tolerance and mercy of the Prophet, may God’s prayers and peace be upon him, to the nation of the call, and his eagerness to dialogue in the best way with non-Muslims, and to ensure their living in a Muslim society, and respect, appreciation and generosity with those who differ in belief and religion, and that steadfastness in the correct belief. And principles do not mean harshness and bad dealing with the violator, nor does it contradict with condescension to him and his mercy in arguing with him with argument and proof in the best way. Keywords: the hadith of the Prophet, coexistence, dialogue, dealing with non-Muslims.